High‐Resolution, Wide‐Field, Forward‐Viewing Spectrally Encoded Endoscope. Issue 9 (26th May 2019) - Zeidan, Adel; Do, Dukho; Kang, Dongkyun; Ikuta, Mitsuhiro; Ryu, Jiheun; Tearney, Guillermo J.
Abstract : Background and Objective: Spectrally encoded endoscopy (SEE) is an optical imaging technology that uses spatial wavelength multiplexing to conduct endoscopy in miniature, small diameter probes. Contrary to the previous side‐viewing SEE devices, forward‐viewing SEE probes are advantageous as they provide a look ahead that facilitates navigation and surveillance. The objective of this work was to develop a miniature forward‐viewing SEE probe with a wide field of view and a high spatial resolution. Materials and Methods: We designed and developed a forward‐viewing SEE device with an overall total diameter of 1.27 mm, which consists of a monolithic illumination probe with a length of 3.87 mm and a diameter of 500 µm, 8 multimode detection fibers that were polished at a 17° angle, a rotational scanning mechanism, and a sheath. The SEE device was evaluated using a USAF resolution target and was used for preclinical imaging of a swine joint ex vivo . Results: This design resulted in a high resolution probe (best spatial resolution of 20.3 µm), a wide total angular field of view of 100°, and an effective number of imaging elements of 344, 000 pixels. The SEE probe performance was compared to a commercial color chip‐on‐the‐tip endoscope; while monochrome, results showed better spatial resolution and a wider field of view for the SEE device. Conclusion: These results demonstrate the potential of this forward‐viewing SEE probe for visualization and navigation in medical imaging applications. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.